A Comprehensive Review for Detection and Prevention Techniques for SQL Injection Attack in Cloud Computing (International Journal of Innovative Research in Engineering & Management, 2022)
In today’s world web applications are  integral part of our day today life. Currently there are  infinite numbers of web users around the world. These web  applications allows users to use the services provided by  them upon justa simple clicks from anywhere in the world.  Due to rapid growth as well as competition in the business  the service providers are making use of the web  applications to attract the user. Some of the common examples of the web applications are banking applications,  social networking applications, ecommerce applications  etc. There exists a variety of attacks that imposes threat on  these web applications. One of such attack is known as  SQL Injection attack. Research has shown that about 64%  of the overall web applications running worldwide are  prone to SQLIA. SQL injection is a SQL code injection  technique, which forces the database to execute malicious  SQL commands that can perform unwanted actions on the  underlying database such as getting access to private  information or even deleting the entire tables or the  database itself. So the prevention against such an attack is  must for the web applications.  Various research work in this area have been carried out so  as to provide better and more accurate defence mechanism  against SQLIA, but still the incident of SQLIA are reported  time and again even with big cloud service providers. This  paper reviews some latest work from some of the best  journals in this area.
Keywords: QL injection attack(SQLIA); Cloud Security; Machine Learning; SQL injection vulnerability; Web applicatio; Structured Query Language